Analysis of the Influence of Capital Adequacy Ratio, Non-Performing Loans, Loan to Deposit Ratio, and Net Interest Margin on Profitability Level (ROA) in Bumn Bank Listed on the IDX for the 2011-2022 Period - Sumiarsih, Sumiarsih; Eddy Irsan Siregar (Jurnal Ekonomi, 2024)
This study aims to analyze the effect of Capital Advocacy Ratio, Non-Performing Loans, Loan To Deposit Ratio, and Net Interest Margin, on the level of Profitability (ROA) in state-owned banks listed on the IDX for the period 2011-2022. The population in this study were four state-owned banks in Indonesia BBRI, BBNI, BBTN, BMRI. The number of samples used was 48. The analysis techniques used in this study include multiple linear regression to understand the comprehensive relationship between the variables concerned. The hypothesis testing methods used include the t-statistic test to test the significance of the partial regression coefficient, and the F-statistic test to evaluate the overall significance with a confidence level of 0.05. In addition, this study also applies classical assumption tests such as normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results of this study indicate that CAR, NPL, LDR, and NIM have a simultaneous effect on ROA in banking companies. The R-square value of 0.862 proves that the model is able to explain 86.2% of its influence on profitability, while the remaining 13.8% is determined by other variables outside the model. This finding implies that bank management can use these variables as a guide in improving the health and financial performance of the bank.